Patterns and Trends in Immediate Postmastectomy Reconstruction in California: Complications and Unscheduled Readmissions. Issue 1 (July 2015) - Merchant, Shaila J.; Goldstein, Leanne; Kruper, Laura L.
Abstract : Background: Immediate reconstruction rates after mastectomy are increasing but remain low. Little is known about hospital readmissions after these procedures. The authors studied unscheduled readmissions after immediate reconstruction. Methods: Using the Healthcare Cost and Utilization Project California State database, the authors identified patients undergoing mastectomy only or with immediate reconstruction for ductal carcinoma in situ and invasive breast cancer from 2005 to 2009. Immediate reconstruction included tissue expander/implant and autologous tissue reconstructions. The authors evaluated temporal trends in immediate reconstruction and factors associated with 30-day unscheduled readmissions after reconstruction. Results: The cohort contained 48, 414 patients (mastectomy only, 35, 648; immediate reconstruction, 12, 766; tissue expander/implant, 10, 437; autologous tissue, 2329). Readmission rates were not significantly different between mastectomy only and immediate reconstruction (3.55 percent versus 3.39 percent; p = 0.39); however, autologous tissue reconstruction was associated with a significantly higher readmission rate compared with tissue expander/implant reconstruction (4.08 percent versus 3.24 percent; p = 0.04). Conclusions: Immediate reconstruction does not result in higher readmission rates compared with mastectomy only. All women undergoing mastectomy should be offered consultation for reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.